Validation of a portable pressure tile system for standing and stepping stability assessment in young and older adults - Kasra Moradi; Brooke E. Peters; Luke Dillman; Chris A. McGibbon (PLoS ONE, 2026)
Portable gait analysis technology for assessing mobility and balance among older adults in community environments remains an underutilized resource, often due to lack of field validation. To address this gap, we used a mixed-validation approach to evaluate a commercially available portable pressure tile system in terms of measurement accuracy: is it true enough to be believed; and sensitivity: can it detect age-related changes in balance and mobility? Thirty healthy adults were recruited in two cohorts of fifteen: YA = 19–64 years of age, and OA = 65 + years of age, to perform a battery of standing and locomotor tasks (static stand = SS, five-times sit-to-stand = STS, step-up/step-down task = SUSD with dominant and non-dominant lead) using a dual elevation, two-tile, StepScan™ pressure tile system placed upon in-floor mounted AMTI™ force platforms for simultaneous data acquisition. Common parameters for balance and stepping analysis were extracted from centre-of-pressure (CoP) kinematics from both systems and analyzed in terms of absolute agreement between systems (paired t-tests and Intra-Class Correlation, ICC(2,k)) and ability to discriminate by age group (independent t-tests and Pearson R 2 ). Agreement between systems was high (<5mm error, ICC > .9) for most measures, and a small but statistically significant decline in balance and mobility performance was detected in the OA cohort compared to the YA cohort (R 2 = .2, p < .05). We conclude that portable, modular, pressure tile systems such as StepScan™ are sufficiently accurate and sensitive for quantifying age-related changes in balance and mobility. Larger scale studies are needed to determine the potential for integrating this technology into routine clinical workflow.